Design and research of wireless charging system of autonomous underwater vehicle based on magnetic coupling resonance. Issue 1 (January 2021) - Yu, Zhimin; Wang, Renzhong
Abstract: In order to apply wireless charging technology to autonomous underwater submersibles, exploring the application of magnetic coupling resonance wireless charging in the field of underwater wireless charging. To expand the application range of autonomous underwater submersibles and improve their endurance. Based on Matlab and multisim 14.0 co-simulation, the wireless charging system flow was designed, and the design of wireless charging device was optimized. Based on the design and modeling analysis of the implementation scheme, the underwater wireless charging system was studied and simulated, and the circuit load resistance was applied. The average power, the average power of the power supply output, the overall efficiency of the circuit, the coupling resonant radio energy transmission efficiency and the coupling coefficient between the coils are compared with theoretical calculations. The simulation results of the wireless charging system of the autonomous underwater submersible with magnetic coupling resonance are highly consistent with the trend of the calculation results, with verification method being effective. The circuit modeling method of underwater wireless charging system is proposed, which provides reference for underwater wireless charging system design. The wireless coupled system with magnetic coupling resonance is a feasible solution for autonomous underwater submersibles, and it is one of the important measures to improve the application performance of autonomous underwater submersibles.